Deaf education in young and adult education modality: bibliographic questions - Silva, Camila Caroline de Lima; Santos, Luciana Araújo dos; de Souza, Shelton (The ESPecialist, 2024)
The present work aims to present considerations about the education of deaf people in the education of young people and adults - EJA. We consider it important to carry out a bibliographical survey using theses and dissertations from the Capes Portal based on scientific productions. This collection of information gave us the opportunity to reflect on what research has been like in Brazil on the descriptors “education of the deaf” and “education of young people and adults”. Regarding the methodological proposal for data generation, we opted for a qualitative approach with bibliographic-analytical procedures. One of the initial results shows a marked lack of work regarding the inclusion of deaf people in EJA, mainly in the Northern region of Brazil, demonstrating the need for work in this vein.